Nonlinear dynamics of relativistic charged particle beams - Nunes, Roger Pizzato (2011)
The idea behind this work is to analyze the transversal dynamics of a relativistic charged particle beam. The beam is azimuthally symmetric, focused by a constant magnetic field and supposed to be initially cold. While mismatched, nonrelativistic, and homogeneous beams oscillate with an invariant cold density profile, it is shown that relativistic homogeneous beams progressively heat and lose an important amount of constituents during its magnetic confinement. This heating process starts with phase-space wave-breaking, a mechanism observed before in initially inhomogeneous beams. The results have been obtained with full self-consistent N-particle beam numerical simulations.